Optimalisasi Pendidikan dan Karir Melalui Digitalisasi di Era Teknologi - Kaurow, Nelfiani; Pusung, Piet Hein; Giroth, Lady Grace Jane; Jacobis, Edwin; Mamahit, Theresa; Putra, Dwikky Trijaya; Putri, Salsabila Pratiwi (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2024)
The use of technology in the digital age is key to optimizing careers and education, as it offers tools and resources that not only expand accessibility but also improve the efficiency and effectiveness of learning and working processes. Digital technologies facilitate access to a wider range of learning resources and training opportunities through e-learning platforms and webinars, while online collaboration tools ease communication and cooperation in international projects. A hybrid digital literacy webinar, i.e., offline and online, was held at SMK Negeri 1 Manado on Tuesday, July 23, 2024. The participants consisted of 80 teachers who participated offline and 220 students who participated online. By utilizing technology, individuals can significantly enhance their capabilities, expand their networks, and achieve career and educational goals more effectively in an increasingly connected world.